COMPETITIVE BUSINESS INDONESIA - M Apun Syaripudin (Proceeding International Conference on Information Technology and Business, 2015)
The purpose of this study was generally is to answer theproblem formulation grains, namely: 1) To analyze howthe Balanced Scorecard through financial and nonfinancialperspectives (customer, internal business processand learning and growth) is used to assess the performanceof the Human Resources companies as part of thecompany's business strategy; 2) To analyze how theinfluence of Non-Financial perspectives (customer,internal business process and learning and growth) affectthe performance of the company's corporate HumanResources. From the perspective of learning and growth ofcompensation indicator indicates that the compensationreceived by employees in the form of salaries andallowances and a maximum deemed not to be scaled backso that employees can be more motivated to work.Meanwhile, indicators of skills and employability(competency) of employees as well as the involvement andactive participation of employees and career developmentwithin the company has been considered relatively.KEY WORDS: Business Performance, Competition AndBalance Scorecard